Quantitative determination of potential genotoxic impurities in metformin hydrochloride and empagliflozin tablets through ultra-performance liquid chromatographymass spectrometry - Xiao, Tingyu; Hu, Xin; Chen, Yucheng; Lin, Huaqing (Journal of pharmaceutical and biomedical analysis, 2024)
An increasing number of drug research institutions consider genotoxic impurity research a core task in drug research and development. Peroxides in drugs may directly or indirectly attack and damage cell DNA, posing a potential carcinogenic risk to the human body. Currently, the literature only studies hydroperoxide impurities, and benzyl peroxide has not been studied yet. In this study, an effective method for ultra-performance liquid chromatographymass spectrometry (UPLCMS/MS) was established and verified to detect and quantify the potential genotoxic impurity (PGI), empagliflozin benzyl peroxide, in metformin–empagliflozin combination formulations, which has not been reported thus far. A Waters ACQUITY UPLC HSS T3 (3.0 ×100 mm, 1.8 µm) column was used to achieve chromatographic separation with gradient elution. The mass spectrometry conditions were optimized using electrospray ionization in the negative mode. Following the International Conference of Harmonization (ICH) guidelines, this methodology can quantify PGIs at 1.35 ng/mL (5.4 ppm) in samples. This validated method exhibited good linearity over a concentration range of 5.4 to 36 ppm, and the accuracy of this method was in the range of 83.2–95.0% for empagliflozin benzyl peroxide. This approach fills the gap in the detection method for benzyl peroxide impurities in metformin hydrochloride and empagliflozin tablets, providing technical support for the quality control of the drug. •A potentially new genotoxic impurity, benzyl peroxide, was identified.•Impurities in metformin–empagliflozin combination formulations were detected.•Hydroperoxide is unstable and produces reactive free radicals that attack DNA.•A method was developed and validated for trace–level quantification of impurities